Proposta de metodologia para o projeto de motores de combustão interna - Antonello, Miguel Guilherme (2015)
The internal combustion engine contributed in replacing animal effort and streamlining production processes. It has been enhanced by the man since its beginnings. Given the wide application of the internal combustion engine and the unavailability of a specific methodology for its development in the modern literature, it becomes clear the importance of knowledge systematization to this product s design. This dissertation presents a methodology to assist in decision making during the process of the internal combustion engine project. The methodology was developed to assist engineering students to develop internal combustion engines to apply mainly didactically, those being led and guided by a set of phases and tasks to reach the ultimate goal. It is also important to highlight the importance of the process of organizing knowledge, as an exemplification and aid tool for product design and design methodology courses. The methodology is structured in six phases: planning and information on the engine design, generation and selection of engine conception, engine concept detailing, engine manufacturing, assembly and engine testing, and finally the engine design closing phase. All phases are composed of a description of the stage, task/sub-task identifier, task/sub-task explanation, person responsible for carrying out the task and the output of the current phase. In addition to the methodology it was developed a spreadsheet with all the information on the phases and it was also provided management and project control tools such as a schedule and two project control charts. After its development, the methodology was assessed by professionals and 68% of the respondents claimed that this method is fully compliant as a helper in an internal combustion engine development process. Therefore, the design methodology expressed in the PMCI reached its initial goal.